Skin Tone's decreasing importance on employment: Evidence from a longitudinal dataset, 1985-2000 - Randall K. Q. Akee; Mutlu Yuksel (Institute for the Study of Labor (IZA), 2010)
We investigate the effect of skin tone on employment probabilities in a longitudinal data set. Using an objective measure of skin tone from a light-spectrometer and a self-reported measure of race we find that over time the effect of skin tone on employment has diminished. These results hold both across the white and African-American samples as well as within the African-American sample itself with regard to skin tone. Further investigation indicates that all of the gains can be attributed to African-American women; there are no changes in the employment probabilities for African-American men in the 15 year panel data. We find that the expansion of employment for women is concentrated in the services occupations.
urn:nbn:de:101:1-201010132754
Keywords: J15; J16; J71; 330; race; gender; employment discrimination; skin tone; panel data